Bilateral Relations Between Indonesia and Malaysia in Handling Illegal Fishing an Maritime Border Areas - Erika Mayasari; Yusuf Ali; Agung Risdhianto (Journal of Social Research, 2025)
This study examines the bilateral cooperation between Indonesia and Malaysia in addressing Illegal, Unreported, and Unregulated Fishing (IUUF) in their shared maritime border areas. The research problem centers on the persistent challenges of IUUF, driven by overlapping jurisdictions, weak surveillance, regulatory disparities, and ineffective cross-border coordination, which collectively threaten maritime sovereignty and resource sustainability. The objectives of this study are to analyze the gaps in current bilateral mechanisms, evaluate implementation challenges, and propose integrated solutions to strengthen cooperation. Using a qualitative approach with descriptive policy analysis, this research employs the Dukeshire & Thurlow Model (2002) to assess actor involvement, institutional effectiveness, and socio-political contexts. Data were collected through literature reviews of policy documents, bilateral agreements, academic publications, and reports from marine research institutions. The results reveal that while both countries have established cooperation frameworks, critical gaps remain in legal harmonization, technological integration, and community participation. Key findings highlight the need for a joint maritime coordination center, harmonized legal standards, and enhanced community-based surveillance. The study concludes that a multidimensional strategy—combining policy alignment, technological innovation, and local empowerment—is essential for effective IUUF mitigation. These findings offer practical implications for policymakers to enhance bilateral maritime governance, ensuring both security and sustainable resource management in the region.